2018
DOI: 10.1093/cid/ciy711
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental Effect of Broad-spectrum Antibiotics on Intestinal Microbiome Diversity in Patients After Allogeneic Stem Cell Transplantation: Lack of Commensal Sparing Antibiotics

Abstract: The use of different types of antibiotic treatment shows different impact on markers of microbiome diversity. Identification of antibiotics sparing commensal bacteria remains an unsolved challenge. However, Rifaximin allowed a higher intestinal microbiome diversity even in the presence of systemic broad-spectrum antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
68
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 42 publications
7
68
1
Order By: Relevance
“…We hypothesize that this difference may reflect higher antibiotic sensitivity of the microbiome after prior insults because most patients in the allo‐HCT cohort had already received chemotherapy and been exposed to antibiotics. Diversity loss was associated with decreased representation of many genera, particularly obligate anaerobes, as demonstrated in previous studies . In contrast, Enterococcus (in both cohorts) and Lactobacillus (in the AL cohort) increased in relative abundance as diversity declined.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…We hypothesize that this difference may reflect higher antibiotic sensitivity of the microbiome after prior insults because most patients in the allo‐HCT cohort had already received chemotherapy and been exposed to antibiotics. Diversity loss was associated with decreased representation of many genera, particularly obligate anaerobes, as demonstrated in previous studies . In contrast, Enterococcus (in both cohorts) and Lactobacillus (in the AL cohort) increased in relative abundance as diversity declined.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies found a correlation between more severe dysbiosis during the peritransplant period and worse clinical outcomes. Greater exposure to anti‐anaerobic antibiotics was associated with increased acute GVHD risk and higher mortality . E‐domination in previous allo‐HCT studies predicted Enterococcus bacteremia .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…30 To our knowledge, few studies have examined the effects of single versus combination antibiotics on the gut microbiome. 31 While we observed a general decrease in diversity in response to antibiotics, our results also showed a distinct impact on microbiota structure and a shift in abundance of specific bacterial ASVs in each treatment group. These findings highlight the need to understand better the additive, antagonistic, synergistic, and non-linear effects of antibiotic treatments with regards to patient outcome.…”
Section: Discussionsupporting
confidence: 46%